Incidence and prognosis of non‐metastatic triple negative breast cancer (TNBC) among different races in Southeast Asia. Issue 5 (7th February 2017) - Alcantara, Veronica Siton; Lim, Geok Hoon; Lim, Swee Ho; Sultana, Rehena; Lee, Jung Ah
Abstract : BACKGROUND AND OBJECTIVES: Triple negative breast cancer (TNBC) carries a worse prognosis compared to the other subtypes. There have been conflicting studies that race may impact the prognosis of TNBC patients. We aim to determine the incidence and prognosis of TNBC among the different ethnic races in Singapore, and to determine its associated risk factors for prognosis. METHODS: Patients diagnosed with invasive breast cancer (BC) from 2005 to 2013 at our tertiary institution were included and divided according to race and subtypes. Demographic and clinical information of non‐metastatic TNBC patients were analyzed. Log‐rank test, univariate and multivariate Cox proportional hazard regression models were used to find associated risk factors related with overall survival (OS) and disease‐free survival (DFS). RESULTS: Among 1227 BC patients, 129 (10.5%) had TNBC. TNBC patients had the worst OS ( P : 0.0005) and DFS ( P : 0.0016) among the subtypes. However, variations in race did not have any difference in OS or DFS among TNBC patients. Axillary lymph node involvement, invasive lobular histology, larger tumor size, and the presence of lymphovascular invasion (LVI) were factors associated with both poor DFS and OS among TNBC patients. CONCLUSIONS: Racial variation did not have any impact on the prognosis of the TNBC.